Nursery Irrigation System Checklist - Tom Yeager (EDIS)
Irrigation must be intensively managed to achieve optimal production times for plants of superior quality. There must be a balance between excessive and inadequate irrigation. Producers use irrigation control devices and past experience to achieve the balance. A few simple checks before and during irrigation can make a big difference in efficient and uniform delivery of the appropriate amount of water. This 4-page fact sheet was written by Tom Yeager, and published by the UF Department of Environmental Horticulture, April 2013.